Plasma homocysteine levels in patients with Psoriasis - Das, Mousumi; Dawn, Indranil; Sarkar, Susmita; Das, Kapildev (Asian Journal of Medical Sciences, 2017)
Background: Hyper homocysteinaemia represents an independent risk factor for atherosclerotic cardiovascular disease, stroke, peripheral arterial occlusive disease and venous thrombosis. Psoriasis is a chronic inflammatory skin disease associated with increased atherothrombosis and cardiovascular risk profile. Aims and Objective: The aim of this study is to investigate homocysteine in psoriatic patients and its relationship with the severity of the disease. Materials and Methods: A case control study in 50 patients with chronic plaque psoriasis and 50 healthy controls was performed. Total plasma homocysteine level, and PASI index were assessed in every patient. Results: Patients with psoriasis had plasma homocysteine levels higher than controls. The severity of psoriasis assessed according to PASI directly correlate either with plasma homocysteine. Conclusion: A significantly higher prevalence of hyperhomocysteinaemia was found in psoriatic patients compared to healthy controls. Our data directly correlate the high level of homocysteine with higher PASI scores. Asian Journal of Medical Sciences Vol.8(5) 2017 4-7